الالتزام بضمان مطابقة المبيع وتمييزه عن الالتزامات الأخرى للبائع: دراسة مقارنة - المعموري، علاء فاضل خلف (جامعة القاهرة - كلية الحقوق - فرع الخرطوم, 2023)
يعد موضوع الالتزام بالمطابقة من المواضيع التي أتت بها اتفاقية فيينا للبيع الدولي للبضائع ۱۹۸۰ إذ جاءت بهذا الالتزام ونصت عليه بصورة صريحة تحديدا في المواد (٣٥- ٤٤) منها باعتباره أحد الالتزامات المفروضة على عاتق البائع ولصالح المشتري، أما بالنسبة للقوانين المدنية سواء في مصر أو في العراق فإنها لم تشر إلى ذلك الالتزام ألا بصورة ضمنية في نصوص قليلة. اختلف الفقه وكذلك القضاء في وضع تعريف للالتزام بضمان المطابقة الإ أن المفهوم البسيط لذلك الضمان يتجلى بكونه ضرورة قيام البائع بتسليم مبيع للمشتري مطابق للمواصفات التي تم الاتفاق عليها في العقد، والإ أصبح من حق المشتري رفض المبيع وتحميل البائع المسؤولية المدنية المترتبة عن ذلك. للالتزام بالمطابقة نوعان: فهو أما التزام بالمطابقة المادية أو التزام بالمطابقة غير المادية (القانونية) الأولى تنقسم إلى أربعة أقسام فهي إما مطابقة كمية أو وصفية أو وظيفية أو مطابقة تعبئة وتغليف، أما الثانية فتنقسم إلى مطابقة قانونية ومطابقة مستندية. إن الالتزام بالمطابقة يقترب أو يتشابه مع الكثير من الأوضاع القانونية المشابهة له، ألا أننا اقتصرنا على تمييز ضمان المطابقة عن التزامات البائع في عقد البيع الأ وهي الالتزام بالتسليم، والالتزام بضمان التعرض والاستحقاق، والالتزام بضمان العيوب الخفية، وأبرزنا أوجه الشبه والاختلاف بين كل منها وبين ضمان المطابقة. The subject of the compliance obligation is one of the topics brought by the Vienna Convention for the International Sale of Goods 1980, as it came with this commitment and explicitly stipulated it specifically in Articles (35-44) of it as one of the obligations imposed on the seller and in favor of the buyer, as for civil laws, whether in Egypt or In Iraq, it did not refer to that commitment except implicitly in a few texts, as we have seen. The jurisprudence and the judiciary differed in defining the obligation to guarantee conformity, but the simple concept of that guarantee is evident in the necessity for the seller to deliver a sale to the buyer in conformity with the specifications agreed upon in the contract, otherwise the buyer has the right to reject the sale and hold the seller responsible for the civil liability resulting from that. The compliance obligation is of two types: it is either a commitment to physical conformity or a commitment to intangible (legal) conformity. The first is divided into four sections, which are either quantitative, descriptive, functional, or packaging conformity. The second is divided into legal conformity and documentary conformity. The obligation of conformity is close or similar to many legal situations similar to it, but we limited ourselves to distinguishing the guarantee of conformity from the obligations of the seller in the sales contract, namely the obligation to deliver, the obligation to guarantee exposure and entitlement, and the obligation to guarantee hidden defects, and we highlighted the similarities and differences between each of them and between Conformity guarantee.
Keywords: عقود البيع -- الالتزامات التعاقدية -- حقوق المشتري -- الاتفاقيات الدولية -- المسؤولية المدنية